Location is Destiny? Unravelling the Income Gap of Gig Workers in Indonesia with Blinder-Oaxaca Decomposition - Hendry Cahyono; Kukuh Arisetyawan; Yusmiaty Sabang; Fariz Al Thoriq; Ardika Tristyanto; Zain Fuadi Muhammad RoziqiFath; Nur Azirah Zahida Mohamad Azhar (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – The objective of this study is to analyze and identify key factors of the income gap between gig workers in urban and rural areas in Indonesia. Secondary data from the 2023 National Socioeconomic Survey (Susenas) was used in this study. Design/methodology/approach – Data analysis was conducted by applying the Blinder-Oaxaca decomposition method to separate the sources of income inequality into components explained by differences in characteristics (endowments) and unexplained components (discrimination or non-observable factors). A robust regression model was also used to ensure the accuracy of the estimates. Finding/Results – This study reveals that gig workers in urban areas have significantly higher incomes (around 12%) than their counterparts in rural areas. Most of this gap is due to differences in characteristics (explained component), particularly access to digital technology and education levels. However, the unexplained component is also significant, indicating differences in market value or discrimination against the same characteristics in both regions. Other factors such as full-time employment, white-collar jobs, male gender, and marital status also positively affect income levels. Originality/Value – The value of this research lies in its primary focus on the long-term impact of spatial inequality among gig workers, as well as its comprehensive use of the Blinder-Oaxaca method in the context of the Indonesian gig economy to describe the sources of this inequality in detail